Efficient ZrO(NO3)2.2H2O Catalyzed Synthesis of 1H-Indazolo[1,2-b] phthalazine-1,6,11(13H)-triones and Electronic Properties Analyses, Vibrational Frequencies, NMR Chemical Shift Analysis, MEP: A DFT Study - Forozan Piryaei; Nahid Shajari; Hooriye Yahyaei (Heteroatom Chemistry)
The synthesis of 1H-indazolo[1,2-b]phthalazine-1,6,11(13H)-trione derivatives, using one-pot three-component condensation reaction of 3-nitrophthalic anhydride, hydrazine monohydrate, dimedone, and aromatic aldehydes in the presence of ZrO(NO3)2.2H2O as the novel catalyst and in reflux conditions in EtOH was reported. Quantum theoretical calculations for three structures of compounds (5a, 5b, and 5c) were performed using the Hartree–Fock (HF) and density functional theory (DFT). From the optimized structure, geometric parameters were obtained and experimental measurements were compared with the calculated data. The structures of the products were confirmed by IR, 1H NMR, 13C NMR, mass spectra, and elemental analyses. The IR spectra data and 1H NMR and 13C NMR chemical shift computations of the 1H-indazolo[1,2-b]phthalazine-1,6,11(13H)-trione derivatives in the ground state were calculated. Frontier molecular orbitals (FMOs), total density of states (DOS), thermodynamic parameters, and molecular electrostatic potential (MEP) of the title compounds were investigated by theoretical calculations. Molecular properties such as the ionization potential (I), electron affinity (A), chemical hardness (η), electronic chemical potential (µ), and electrophilicity (ω) were investigated for the structures. Thus, there was an excellent agreement between experimental and theoretical results.